Effect of oil palm bio-organic wastes on macro-propagation of some permanent crops’ seeds - Wasiu Lamidi; Janet Dada (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Research investigated oil mill decanter cake (OPDC) and empty fruit bunch (EFB) from oil palm in varying forms as soil media for growth performances of cocoa (Theobroma cacao) and citrus (Citrus sp.) seeds during germination and growth.Method: Factorial design with 4 levels of bio-organic: oil palm decanter cake (OPDC) treated with hot water at 70 oC, OPDC treated with hot water at 80 oC, OPDC raw and EFB; 2 levels of crops: citrus and cocoa seedlings were investigated. Each treatment was replicated thrice (4 × 2 × 3). A control experiment with normal sandy clay loam soil (NSCLS) medium, was also replicated thrice. Plant height; stem girth, number of leaves, days to seeds' emergence, leaf area, and biomass were measured.Results: Days to emergence, number of leaves, and stem girth of cocoa seedlings were significantly different (p≤0.05) with different forms of OPDC media and EFB. Maximum growth performance was obtained for EFB, the highest number of leaves was 17.33, stem girth, 1.32. EFB has the least number of days of emergence. OPDC has high moisture and nutrient content.  OPDC and EFB have lesser bulk density compared with soil medium. Biomass gains from using bio-organic wastes as soil media for the cocoa and citrus seedlings were as high as 263.5 g (citrus), 237.5 g (cocoa) for EFB and they were the highest.Conclusion: Incorporation of OPDC and EFB as bio-organic media would boost nursery growth of permanent crops.